Effect of Listening to Gangster Music on the Behaviors of Generation Z: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aimed to learn about the effects of listening to gangster rap music. The researchersobserved that music could be found almost anywhere, and it can easily be accessible viaradios, various recordings, the internet, and new technologies; however, according to thestudies, music could highly influence our behavior. The researchers specified that music couldcause young audiences to behave badly.Furthermore, researchers have found out that the more you listen to gangster rap music, themore it can affect your lifestyle, the way you talk, your outfit, and your use of curse words. Withproper parenting and giving advice as to what music they should avoid, their children wouldgrow to know what music is bad for them.The researchers would like to recommend this study to Generation Z, who are prone to thiskind of music, to be conscious of what music they should listen to because it could influencetheir behaviors, as well as future researchers, in order to expand this study case theparticipants to know more bout this study. Overall, the discussion in this subsectionemphasizes the importance of being mindful of the music we listen to and the potentialinfluence it can have on our behavior.
Keywords: Clinical Psychology